Some issues of the practical application of the knowledge in students’ extracurricular activities - Grabauskienė, A. (Psichologija, 1962)
The article discusses the issue of the practical application of the knowledge in students’ extracurricular activities. This issue is still poorly addressed both in pedagogical theory and school practice. We view the practical application of knowledge in students’ extracurricular activities as a bridge to help connect learning with life and move away from application of knowledge in learning activities to real-life applications. This article demonstrates that students face major difficulties not only in transferring knowledge and skills from school to life but also from class to extracurricular activities. Basically, these difficulties are related to how similar students’ extracurricular activity is to life activities in terms of conditions, tasks, the gravity, and the broader application of knowledge and skills. Therefore, the logic of knowledge and skills application in extracurricular activities is more akin to their application in life, and the logic of the application of knowledge in life is totally different from the application of knowledge in learning activities. The pupil who easily applies knowledge in the classroom for learning purposes will find it more difficult to cope with the application of the same knowledge in extracurricular practice. This can be explained by the new challenges and relationships continually arising in life, while the classroom routine is left behind. Students need to be able to use their knowledge more independently and without the teacher. Besides, the application of knowledge in extracurricular activities also requires the application of many skills, and the application of skills typically lags behind the application of knowledge. In order for students to overcome these tasks, you need to spend a long time teaching them to apply the knowledge not only in class activities, but also in after school events. By applying knowledge and skills this way students develop new motives for application and improve the knowledge and skills; the activity can more often be characterized as independent and creative. Students begin to see and that they the knowledge and skills acquired through study can be applied to solving tasks in real life. All this makes it possible to apply knowledge gained in real life.